1996
DOI: 10.1038/381706a0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of synaptic responses to high-frequency stimulation and LTP by neurotrophins in the hippocampus

Abstract: Neurotrophins promote neuronal survival and differentiation, but the fact that their expression is modified by neuronal activity, suggests a role in regulating synapse development and plasticity. In developing hippocampus, the expression of brain derived neurotrophic factor (BDNF) and its receptor TrkB increases in parallel with the ability to undergo long-term potentiation (LTP). Here we report a mechanism by which BDNF modulates hippocampal LTP. Exogenous BDNF promoted the induction of LTP by tetanic stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
727
7
9

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,041 publications
(800 citation statements)
references
References 29 publications
46
727
7
9
Order By: Relevance
“…Although NGF perfusion in hippocampal slices (Tancredi et al, 1993) has been reported to block the long-term potentiation (LTP) appearance, other papers have shown no NGF effects on hippocampal and visual cortex plasticity (Khang and Schuman, 1995;Figurov et al, 1996;Akaneya et al, 1997) Moreover, local TrkA activation in primary visual cortex (Pizzorusso et al, 1999) and in vivo NGF injection into the lateral ventricles (Maffei et al, 1992;Lodovichi et al, 2000) counteract the ocular dominance distribution of visual cortical neurons in monocularly deprivated rats. In addition, the blockage of endogenous NGF also interferes with the rat visual system maturation by influencing the critical period Domenici et al, 1994) and exogenous NGF supply favors longterm depression (LTD) over LTP in visual cortical layer II-III of 16 to 18-day-old rats (Pesavento et al, 2000;Brancucci et al, 2004).…”
Section: Ngf Bdnf and Synaptic Plasticitymentioning
confidence: 99%
“…Although NGF perfusion in hippocampal slices (Tancredi et al, 1993) has been reported to block the long-term potentiation (LTP) appearance, other papers have shown no NGF effects on hippocampal and visual cortex plasticity (Khang and Schuman, 1995;Figurov et al, 1996;Akaneya et al, 1997) Moreover, local TrkA activation in primary visual cortex (Pizzorusso et al, 1999) and in vivo NGF injection into the lateral ventricles (Maffei et al, 1992;Lodovichi et al, 2000) counteract the ocular dominance distribution of visual cortical neurons in monocularly deprivated rats. In addition, the blockage of endogenous NGF also interferes with the rat visual system maturation by influencing the critical period Domenici et al, 1994) and exogenous NGF supply favors longterm depression (LTD) over LTP in visual cortical layer II-III of 16 to 18-day-old rats (Pesavento et al, 2000;Brancucci et al, 2004).…”
Section: Ngf Bdnf and Synaptic Plasticitymentioning
confidence: 99%
“…Recent work has confirmed this broad idea by identifying both positive and negative factors that modulate LTP under naturalistic circumstances. The neurotrophin brain-derived neurotrophic factor (BDNF) is the most potent facilitator of LTP yet discovered (Figurov et al, 1996;Akaneya et al, 1997;Kang et al, 1997;Bramham and Messaoudi, 2005). BDNF is synthesized by hippocampal and cortical pyramidal cells (among others), anterogradely transported to axon terminals (Altar et al, 1997;Conner et al, 1998), and released by theta burst stimulation (Balkowiec and Katz, 2000).…”
Section: Redundancy and Modulation In Ltpmentioning
confidence: 99%
“…Specifically, soluble Aβ oligomers are fundamental to promote neurotoxicity (Klein, 2001; Walsh & Selkoe, 2007) through different ways (Ferreira & Klein, 2011; Pearson‐Leary & McNay, 2012), including altered levels of neurotrophic factors (NTFs) (Calissano et al ., 2010; Budni et al ., 2015). Among these, brain‐derived neurotrophic factor (BDNF) (Barde et al ., 1982) is essential in sustaining physiological processes of the normal adult brain (Nagahara & Tuszynski, 2011), by tuning: (i) dendritic branching and spine morphology (Horch & Katz, 2002) and (ii) synaptic plasticity and long‐term potentiation (Figurov et al ., 1996) and therefore learning and memory. Interestingly, postmortem studies have shown that BDNF mRNA and protein decrease not only in end‐stage disease, but also in patients diagnosed with mild cognitive impairment (MCI) (Peng et al ., 2005), suggesting that a BDNF loss could be involved in the early synaptic dysfunctions.…”
Section: Introductionmentioning
confidence: 99%